2014
DOI: 10.1371/journal.pmed.1001742
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c Levels and Risk of Severe Hypoglycemia in Children and Young Adults with Type 1 Diabetes from Germany and Austria: A Trend Analysis in a Cohort of 37,539 Patients between 1995 and 2012

Abstract: In a cohort study, Beate Karges and colleagues find that the association between low hemoglobin A1C and severe hypoglycemia in children and young adults with type 1 diabetes has decreased over the period between 1995 and 2012. Please see later in the article for the Editors' Summary

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
130
6
10

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 133 publications
(162 citation statements)
references
References 36 publications
16
130
6
10
Order By: Relevance
“…No association between lower HbA1c and hospital admission rate for severe hypoglycemia was found, similar to other reports (9,13). These results correspond to our previous findings in young individuals with type 1 diabetes that low HbA1c no longer predicts the risk of severe hypoglycemia (8).…”
Section: European Journal Of Endocrinologysupporting
confidence: 91%
See 3 more Smart Citations
“…No association between lower HbA1c and hospital admission rate for severe hypoglycemia was found, similar to other reports (9,13). These results correspond to our previous findings in young individuals with type 1 diabetes that low HbA1c no longer predicts the risk of severe hypoglycemia (8).…”
Section: European Journal Of Endocrinologysupporting
confidence: 91%
“…The Diabetes Patienten Verlaufsdokumentation (DPV) Prospective Documentation Initiative of diabetes care in Germany has prospectively followed patients with diabetes mellitus since 1995 (1,8). Analysis of anonymized data was approved by the Ethics Committee of Ulm University, Ulm, Germany.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a number of more recent studies have not confirmed the strong association between optimization of glycemic control and an increase in risk of SH in children, adolescents, and adults. [18][19][20][21][22][23][24] Nevertheless, CGM might be a technical solution assisting the achievement of both treatment goals. It is of interest to note that in a recent publication no indication was found that CGM usage reduces SH, fear of hypoglycemia, hypoglycemia awareness, or even biochemical hypoglycemia.…”
Section: Risk Of Hypoglycemic Events In Patients With Type 1 Diabetesmentioning
confidence: 99%